Intracranial atherosclerotic plaque enhancement and long‐term risk of future strokes: A prospective, longitudinal study. Issue 2 (19th December 2022) - Gómez‐Vicente, Beatriz; Hernández‐Pérez, María; Martínez‐Velasco, Elena; Rodríguez‐Velasco, Margarita; Munuera, Josep; Rubiera, Marta; Vert, Carla; Dorado, Laura; de Lera, Mercedes; Calleja, Ana Isabel; Cortijo, Elisa; Agulla, Jesús; et al.
Abstract: Background and Purpose: The prognostic significance of postcontrast enhancement of intracranial atheromatous plaque is uncertain. Prospective, long‐term follow‐up studies in Caucasians, using a multicenter design, are lacking. We aimed to evaluate whether this radiological sign predicts long‐term new stroke in symptomatic and asymptomatic intracranial atherosclerotic disease (ICAD) patients. Methods: This was a prospective, observational, longitudinal, multicenter study. We included a symptomatic and an asymptomatic cohort of ICAD patients that underwent 3T MRI including high‐resolution sequences focused on the atheromatous plaque. We evaluated grade of stenosis, plaque characteristics, and gadolinium enhancement ratio (postcontrast plaque signal/postcontrast corpus callosum signal). The occurrence of new events was evaluated at 3, 6, 9, and 12 months and annually thereafter. The association between plaque characteristics and new stroke was studied using Cox multiple regression survival analysis and Kaplan‐Meier curves. Results: Forty‐eight symptomatic and 13 asymptomatic patients were included. During 56.3 ± 16.9 months, 11 patients (18%) suffered a new event (seven ischemic, two hemorrhagic, and two transient ischemic attacks). A receiver operating characteristic curve identified an enhancement ratio of >1.77 to predict a new event. In a multivariable Cox regression, postcontrast enhancement ratio >1.77 (hazard ratio [HR]= 3.632; 95% confidence interval [CI], 1.082‐12.101) and cerebral microbleeds (HR = 5.244; 95% CI, 1.476‐18.629) were independent predictors of future strokes. Patients with a plaque enhancement ratio >1.77 had a lower survival free of events ( p < .05). Conclusions: High intracranial postcontrast enhancement is a long‐term predictor of new stroke in ICAD patients. Further studies are needed to elucidate whether postcontrast enhancement reflects inflammatory activity of intracranial atheromatous plaque.